2015
DOI: 10.1111/1440-1681.12485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of minocycline on parameters of cardiovascular recovery after cardioplegic arrest in a rabbit Langendorff heart model

Abstract: Pharmacological cardiac organ protection during cardiopulmonary bypass presents an opportunity for improvement. A number of different strategies have been established to minimize ischemia/reperfusion-induced damage to the heart. Among these, cardioplegia with histidine-tryptophan-ketoglutarate solution and hypothermia are the most frequently used regimens. The antibiotic minocycline has been used in this context for neuroprotection. The aim of the current study was to evaluate whether the application of minocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…For our experiments we used mature female and male Chinchilla rabbits weighting 1,500–2,000 g. Preparation of the hearts and perfusion according to the Langendorff-technique was performed as described earlier (Salameh et al, 2015b). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For our experiments we used mature female and male Chinchilla rabbits weighting 1,500–2,000 g. Preparation of the hearts and perfusion according to the Langendorff-technique was performed as described earlier (Salameh et al, 2015b). …”
Section: Methodsmentioning
confidence: 99%
“…Histological evaluation of the ventricular probes was carried out according to Salameh et al (2015b), in order to analyze the presence of the pro-apoptotic factor AIF (apoptosis inducing factor), PAR (poly-ADP-ribose)-formation, HIF1α hypoxia induced factor 1α-translocation and cC3 (cleaved caspase 3)-levels as well as nitrotyrosine formation and HSP60 (heat shock protein 60)-levels. Specimens embedded in paraffin were cut in 2 μm slices, de-paraffinized and treated with 0.3% Triton-X 100 (for nitrotyrosine-staining) or cooked in 0.01 mol/L citrate buffer ( pH = 6) (for AIF-, HIF1α-, PAR-, cC3-, and HSP60-staining).…”
Section: Methodsmentioning
confidence: 99%
“…For histological analysis, hearts were processed according to Salameh et al (2015). Briefly, formalin-fixed hearts were embedded in paraffin and sectioned into 2 µm slices.…”
Section: Histologymentioning
confidence: 99%
“…Left ventricular specimen were homogenized on ice with 0.4 mmol/L perchloric acid and precipitated with KOH. The samples were centrifuged and supernatants were injected twice onto a pre-equilibrated RP18 column (LiChroCART, Merck, Darmstadt, Germany) as previously published (Salameh et al, 2015). For ATP detection a HPLC-apparatus from Knauer (Berlin, Germany) and an UV-detector (PDA Detector 2800, Knauer, Berlin, Germany) were used.…”
Section: Atp Analysis By Hplcmentioning
confidence: 99%
“…Expanding from neuroprotection to possible cardioprotection, several preclinical studies administered minocycline in cardioplegia and in ischemia/reperfusion injury models and found beneficial results. 17,18 Further studies investigated mechanisms and found that minocycline reduces/inhibits several important mediators of inflammation and apoptosis including high mobility group box 1 protein (HMGB1) an early mediator of inflammation and poly(ADP-ribose) polymerase-1 (PARP-1) extensively activated in ischemic tissue where it releases apoptotic-inducing factors. 19,20 In this current study, the investigators used micro-SPECT/CT imaging to demonstrate lower uptake of GSAO in risk regions of minocycline-treated rabbits compared to saline-treated control rabbits.…”
Section: See Related Article Pp 94-100mentioning
confidence: 99%